Age and Gender Differences with Clinical Presentation of Patients with Histopathological and CT-Scan Confirmed Parapharyngeal Mass - Khanam, Rehana; Khanam, Shafeya; Kabir, Tasnia; Kabir, Ehsanul (Journal of Current and Advance Medical Research, 2023)
Background: Parapharyngeal Mass can occur in different age and gender group with varied clinical features. Objective: The purpose of the present study was to see the age and gender differences with clinical presentation of patients with histopathological and CT-scan confirmed parapharyngeal mass. Methodology: This was a cross sectional type of study. This study was carried out in the Department of Radiology and Imaging at Dhaka Medical College, Dhaka, Bangladesh. This study was carried out from January 2014 to December 2016. Clinically suspected cases of para pharyngeal space mass lesions attended in the otolaryngology and Radiology & Imaging department of Dhaka Medical College, Dhaka, Bangladesh were enrolled in this study. The patient in this study was evaluated according to the management plan for surgery followed in Otolaryngology department, which includes History, Clinical examination, CT-scan and Histopathology. Detail history about the illness, chief complains taken in formatted history sheet. All patients were undergone CT examination of neck in the Department of Radiology and Imaging at Dhaka Medical College, Dhaka. After resection of the mass, the specimen was sent to histopathological examination to the Department of Pathology at Dhaka Medical College, Dhaka, Bangladesh. Results: Male and female ratio was 2.57:1. Maximum 54% patients were belonged to 21-40 years’ age group followed by 38% 41 and above age group and 8.0% up to 20 years’ age group. Mean (±SD) age of the patients was 37.76 (14.82). Presence of mass, fever, malaise, pain, otalgia or fullness in ear, dysphagia, facial nerve dysfunction, trismus, dyspnea and deviation of tongue were the main presenting features of this study. Out of all lesions 58% were in left parapharyngeal space and 42% were in right. Of all patients, 20% had nerve sheath tumour (14% schwannoma & 6% neurofibroma), 6% had paraganglioma, 14% had chronic nonspecific lymphadenitis, 12% had tuberculosis, 16% had squamous cell carcinoma (invasion from adjacent spaces). Parotid pleomorphic adenoma (6%) & mucoepidermoid carcinoma (4%). Rests had, lipoma (4.0%), branchial cleft cyst (4.0%), lymphoma (6.0%), and abscess (2.0%). After histopathological evaluation 24% were malignant and 76% were benign. Conclusion: In conclusion majority of the study population are young adult male presented with mass, fever and malaise. Journal of Current and Advance Medical Research, January 2023;10(1):25-30